Effectiveness of fixed dose combination medication ('polypills') compared with usual care in patients with cardiovascular disease or at high risk: A prospective, individual patient data meta-analysis of 3140 patients in six countries. (15th February 2016) - Webster, Ruth; Patel, Anushka; Selak, Vanessa; Billot, Laurent; Bots, Michiel L.; Brown, Alex; Bullen, Chris; Cass, Alan; Crengle, Sue; Raina Elley, C.; Grobbee, Diederick E.; Neal, Bruce; et al.
Abstract: Aims: To conduct a prospective, individual participant data (IPD) meta-analysis of randomised controlled trials comparing a polypill-based approach with usual care in high risk individuals. Methods and results: Three trials comparing polypill-based care with usual care in individuals with CVD or high calculated cardiovascular risk contributed IPD. Primary outcomes were self-reported adherence to combination therapy (anti-platelet, statin and ≥ two blood pressure (BP) lowering agents), and difference in mean systolic BP (SBP) and LDL-cholesterol at 12 months. Analyses used random effects models. Among 3140 patients from Australia, England, India, Ireland, New Zealand and The Netherlands (75% male, mean age 62 years), median follow-up was 15 months. At baseline, 84%, 87% and 61% respectively were taking a statin, anti-platelet agent and at least two BP lowering agents. At 12 months, compared to usual care, participants in the polypill arm had higher adherence to combination therapy (80% vs. 50%, RR 1.58; 95% CI, 1.32 to 1.90; p < 0.001), lower SBP (− 2.5 mmHg; 95% CI, − 4.5 to − 0.4; p = 0.02) and lower LDL-cholesterol (− 0.1 mmol/L; 95% CI, − 0.2 to 0.0; p = 0.04). Baseline treatment levels were a major effect modifier for adherence and SBP (p-homog < 0.0001 and 0.02 respectively) with greatest improvements seen among those under-treated at baseline. Conclusions: Polypill therapy significantly improved adherence, SBP and LDL-cholesterol in high risk patients compared with usual care, especially among those who were under-treated at baseline.